Antibiotics in eosinophilic chronic rhinosinusitis: Rethinking maximal antimicrobial medical therapy. (26th November 2016) - Günel, Ceren; Bleier, Benjamin S.; Meteoglu, Ibrahim
Abstract : Objectives/Hypothesis: Eosinophilic chronic rhinosinusitis (eCRS) has recently been recognized as a CRS subtype characterized by inflammation rather than chronic infection. Consequently, the role of antibiotics as a component of maximal medical therapy for eCRS has been called into question. The purpose of this study was to investigate whether the use of antibiotics, which lack any secondary anti‐inflammatory properties, are useful in the treatment of eCRS. Study Design: Prospective individual cohort study. Methods: Institutional review board–approved, prospective study of 39 patients presenting with chronic rhinosinusitis (CRS). In all patients, Lund‐Kennedy endoscopy scores, Lund‐Mackay computed tomography scores, and Sino‐Nasal Outcome Test‐22(SNOT‐22) scores were obtained before and after treatment with amoxicillin–clavulanic acid twice a day (625 mg) for 4 weeks. Patients were subsequently stratified into eCRS and non‐eCRS groups based on having over 10 eosinophils per high‐power field by histopathological examination. The efficacy of antibiotic therapy was compared between groups using the nonparametric Mann–Whitney U test. Results: Within the non‐eCRS group (n = 14), there was a significant improvement in both the Lund‐Mackay score ( P = .002) and SNOT‐22 score ( P < .001) but not the endoscopy score. Among the eCRS patients (n = 25), the Lund‐Mackay score was similarly improved ( P = .007); however, there was no significant improvement in the endoscopy or SNOT‐22 scores. Conclusions: The use of antibiotics without independent anti‐inflammatory properties have limited efficacy in patients with eCRS. The concept of maximal medical therapy using antibiotics must continue to evolve in the setting of new evidence for inflammatory subtypes of CRS. Level of Evidence: 2b. Laryngoscope, 127:794–796, 2017